Teknik Prompt ANVS Progresif untuk Bing Image Creator dan Interpretasi Kesenjangan Gambar AI - Darmawan, Andreas James; Hyuk Yoo, Peter Min; Hartawan, Rivandy Aprilian (Universitas Komputer Indonesia, 2024)
In the increasingly developing digital era, the mastery of artificial intelligence (AI) image generator technology has become a popular tool for designers, artists, and general users to create images that suit user needs. However, many users still face difficulties in getting image results that meet user expectations. This research is qualitative, trying to gradually create prompts by evaluating the results in order to understand the image creation process from Bing Image Creator. The author developed and tested a formula called ANVS; namely: Adjective, Noun, Verb, and Style, which is designed to help users design effective prompt engineering. This formula is gradually used in developing prompts, starting from simple to quite complex, to explore how each component in ANVS can affect the image results produced by Bing Image Creator. The results of the research are in the form of recording the use of prompts and image results from Bing Image Creator. It is hoped that this research can help in creating the right prompt to produce images that suit user needs, especially for users of the Bing Image Creator platform and/or other similar AI image generators.